Billy and the Bees - Wragg, Ted (UK, 1994)
Billy and One Tooth went to the park with Grandad. 'Can we have an ice cream, please?' said Billy. Grandad got three pink ice creams. Grandad and Billy ate there ice cream. But One Tooth ate most of his ice cream! But he got ... Ice cream on his hand, arm, nose, hair,and ears. There was pink ice cream all over the place. Just then a big bee flew by 'Bzzz! Bzzz! Bzzz!'...
Keywords: Adventure; Juvenile Fiction